Privatizing the Church: Disestablishment in Connecticut and Massachusetts - Olds, Kelly (Journal of Political Economy, 1994)
Tax-supported churches were established in most American colonies. Public Congregationalist churches in New England were not privatized until the early nineteenth century. After privatization, demand for preachers rose rapidly. There is weaker evidence that church membership also rose quickly. The increase in preachers came almost totally from private denominations. The privatization of religion was further accompanied by a change in methods of finance.